Flora Lexicons in Acehnese Proverb: Ecolinguistic Study - Mubshirah, Dara; Widayati, Dwi; Mbete, Aron Meko; Dardanila (International Journal Linguistics of Sumatra and Malay, 2024)
This study aimed is to examine flora lexicons in Acehnese Proverbs. This study used a qualitative approach with descriptive and a content analysis method. This data was analysed using the Miles and Huberman method; the data source for this research was Hasyim's book (1977) of Acehnese proverbs. The result showed that The flora lexicon found in Acehnese proverbs in the form of nouns includes Bak mee (tamarind), Trieng (bamboo), Reuböng (bamboo shoots), Beuringén (banyan), Kacang (peanut), U (coconut), Teubèe (sugarcane), Pineung (areca), Labu (pumpkin), Mangga (mango), Panah (jackfruit). Acehnese proverbs that use flora/botanical analogies are used to express satire, advice, and wisdom.